2009
DOI: 10.1073/pnas.0909409106
|View full text |Cite
|
Sign up to set email alerts
|

A t-butyloxycarbonyl-modified Wnt5a-derived hexapeptide functions as a potent antagonist of Wnt5a-dependent melanoma cell invasion

Abstract: The influential role of Wnt5a in tumor progression underscores the requirement for developing molecules that can target Wnt5a-mediated cellular responses. In the aggressive skin cancer, melanoma, elevated Wnt5a expression promotes cell motility and drives metastasis. Two approaches can be used to counteract these effects: inhibition of Wnt5a expression or direct blockade of Wnt5a signaling. We have investigated both options in the melanoma cell lines, A2058 and HTB63. Both express Frizzled-5, which has been im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
115
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 36 publications
16
115
1
Order By: Relevance
“…Wnt5a has been reported to activate the non-canonical pathway and induce migration of human melanoma cell line A2058 (ref. 16). We further used Wnt5a to examine the inhibitory role of LRP5/6 in endogenous Frz in A2058 cells.…”
Section: Lrp6 Interacts With Frz Independently Of Wnt Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt5a has been reported to activate the non-canonical pathway and induce migration of human melanoma cell line A2058 (ref. 16). We further used Wnt5a to examine the inhibitory role of LRP5/6 in endogenous Frz in A2058 cells.…”
Section: Lrp6 Interacts With Frz Independently Of Wnt Ligandsmentioning
confidence: 99%
“…The non-canonical Wnt5a can promote normal cell motility as well as tumour metastasis through the activation PCP/JNK or Ca 2 þ /PKC signalling cascade [16][17][18] . Thus, noncanonical pathways are involved in cancer development through promoting tumour cell motility.…”
mentioning
confidence: 99%
“…Another chemical modulator used in our studies is Box5, a Wnt5a-derived hexapeptide which has been shown to antagonize activities mediated by Wnt5a and Fz5 such as calcium response, cell invasion and migration in tumor cell lines (Jenei et al, 2009). Wnt5a can also bind Ror2 and this interaction is well established and classified as a separated branch of the Wnt pathway, namely Wnt5a/Ror2 pathway (Grenn et al, 2008, Minami et al, 2010.…”
mentioning
confidence: 99%
“…DVL antagonises destruction complex activity, causing β-catenin accumulation to allow nuclear translocation where in consort with the T-cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors, β-catenin elicits activation of WNT target gene expression (Cadigan 2012). WNT/β-catenin-independent signaling commonly occurs through Ca 2+ signaling in tumours, resulting in activation of Ca 2+ -dependent enzymes to elicit transcriptional changes and increase small GTPase activity, causing cytoskeletal rearrangements and alteration of cell polarity/migration (Jenei, et al 2009). …”
Section: Wnt Signaling In Cancermentioning
confidence: 99%
“…However a WNT5A-derived hexapeptide, termed Box5, 12 developed to inhibit WNT/Ca 2+ signaling in melanoma (Jenei, et al 2009), has recently been shown to antagonise WNT5A/Ca 2+ signaling in HNSCC (Prgomet, et al 2015). Future efforts should be focused on identifying which WNT network inhibitors could provide potent therapeutic activity in cSCC.…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%